Assessing the Print Communication and Technology Attributes of an Academic Medical Center - Kelsey Leonard; Sandy Oelschlegel; Emily Tester; Jennifer Russomanno; Eric Heidel (SLACK Incorporated, 2018)
Background: Historically, health literacy has been viewed as the patient's problem; however, it is now accepted that the responsibility for improving health literacy lies with the health care professionals and systems. An Institute of Medicine report outlines the health literacy attributes, such as printed patient education and technology, which both play a role in patient decision-making and engaging them in their health care. Research suggests that patients who are engaged in their health care have improved health outcomes. For health care organizations to accommodate the needs of all patients, it is imperative that they determine the current organizational state and discover opportunities for improvement. Methods: The Health Literacy Environment of Hospitals and Health Centers (HLEHHC) Print Communication Rating and Technology Rating Tool were used to measure the internal aspects of organizational health literacy at The University of Tennessee Medical Center (UTMC). Included in the print assessment were the 150 most distributed patient education handouts. Researchers also used the Simple Measure of Gobbledygook and Patient Education Materials Assessment Tool to assess print material. Technology was assessed using UTMC's website as the authoritative source. Key Results: The HLEHHC was useful for assessing print material and technology. Reviewing and reporting the data question-by-question revealed more granular, actionable information on where there are opportunities to improve the health care environment for all patients. This analysis resulted in proposing actions based on best practices that UTMC could implement in the coming year. The process is replicable in other settings. Implications: Responsibility for improving informed medical decision-making lies with health care organizations. Low health literacy influences the effectiveness of print patient education and technology in informing patients about their health. Assessing these aspects of the health care organization as part of quality improvement provides necessary data for improvements. The Health Literacy Environment of Hospital and Health Centers was a useful tool to measure characteristics of print and technology.